1.9 μm lasing with Tm3+/Yb3+ co‐doped air‐clad fiber and 931 nm pumping. Issue 5 (23rd March 2013) - Saidin, N.; Halder, A.; Ghosh, D.; Pal, M.; Paul, Mukul Chandran; Bhadra, S. K.; Ali, S. M. M.; Damanhuri, S. S. A.; Ahmad, H.; Harun, Sulaiman Wadi
Abstract A 1.9 μm single mode laser is demonstrated by employing a newly developed large mode area Tm3+/Yb3+ co‐doped air‐clad photonic crystal fiber (PCF) in conjunction with 931 nm pumping for the first time. The PCF has an Yb3+ and Tm3+ ion concentrations of about 16 × 10−19 and 4 × 10−19 ions/cc, respectively. The laser produces a maximum output power of 4.6 mW with an efficiency slope of 0.70% at a multimode pump power of 2.3 W with a 2.7 m long PCF in a linear cavity with two fiber Bragg grating. The threshold of the input pump power is obtained at around 1.3 W. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1124–1126, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27523